Flash vapor fuel injector development. (August 2016) - Zhang, Xiaohua; Palazzolo, Alan; Tucker, Randall; Kascak, Albert; Kweon, Chol-Bum
Following the single-fuel initiative, the US Army is transitioning its power plants from running on various fuels to a single fuel—JP-8. Due to its low vapor pressure, JP-8 could not be used to cold start or run gasoline engines without extensive retrofit. The feasibility of running a low compression ratio, spark ignition engine with direct injection of heated JP-8 was investigated. A preliminary study found that a small piston-type spark ignition engine would not start or run on JP-8 unless JP-8 was heated to certain temperature. JP-8's thermal decomposition, or coking, was found to be a serious issue that must be addressed if fuel heating method would be used. A flash heater concept was proposed to solve problems of JP-8's low vapor pressure on running low compression ratio spark ignition engines, as well as JP-8's coking issue at high temperature. A flash vapor fuel injector was designed and tested to be capable of heating up JP-8 from 26.7 °C to its vaporization temperature of >154.4 °C under one-tenth of a second at the required flow rate. The longest duration heating test (>1 million injections) did not show any coking sign with flash heating. Ignition test results show equivalent or superior ignition characteristics of pre-heated JP-8 (with heater temperature at 260.0 °C or above) provided by the developed flash vapor fuel injector, compared with non-heated aviation gasoline.